FINANCIAL PERFORMANCE ANALYSIS USING PROFITABILITY RATIO ATPT. SUPARMA TBK 2020-2022 - Shindu Hargo Dedali (Universitas Maarif Hasyim Latif, 2023)
This study aims to analyze the financial performance of PT. Suparma Tbk, which looks at the profitability factor by using the Gross Profit Margin Ratio and the Net Profit Margin Ratio, 2020-2022. This research is descriptive quantitative. The research data was obtained from the Financial Statements of PT. Suparma Tbk in 2020-2022. Data were analyzed using profitability ratios by using the gross profit margin ratio and the net profit margin ratio. This study shows: 1) The financial performance of PT. Suparma Tbk, which looks at the profitability factor using the Gross ProfitMargin Ratio, in 2020, 2021 and 2022 in a healthy condition and 2) The financial performance of PT. Suparma Tbk, which looks at profitability using the Net Profit Ratio, in 2020, 2021 and 2022 in a healthy condition. And the results ofthis study show that the Gross Profit Margin Ratio and the Net Profit Margin Ratio for 2020-2022 have healthy performance, so that the Management of PT. Suparma Tbk must maintain sales and further increase product sales by more aggressively promoting and offering products to new customers. And maintaining old customers so that they always repeat orders so that the company's profits continue to increase every year.